Reduction of Mutual coupling in Microstrip Array Antenna using Polygonal Defected Ground Structure - Farahbakhsh, Ali; Moradi, Gholamreza; Mohanna, Shahram (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The surface wave propagation is a significant problem in microstrip array antennas. Several methods have been reported to suppress the propagation of surface wave such as defected ground structure (DGS). The main problem in DGS is to determine the shape of ground slot. In this paper, a new method is proposed in which the slot is assumed to be a polygon and its shape is obtained by enhanced genetic algorithm (GA) and ant colony optimization (ACO) to have an array antenna with good gain and the least amount of return loss and mutual coupling.